Вроджений гіпотиреоз: клініка, діагностика, лікування - Хижняк, О. О. (Clinical Endocrinology and Endocrine Surgery, 2009)
Lecture article covers etiology, clinical manifestation, diagnostics, observation and treatment of children with congenital hypothyroidism.